On the Form Drag Coefficient Under Ridged Ice : Laboratory Experiments and Numerical Simulations From Ideal Scaling to Deep Water - Zu, Y.; Lu, P.; Leppäranta, Matti; Cheng, B.; Li, Z. (Journal of Geophysical Research: Oceans, 2021)
The bottom topography of ridged sea ice differs greatly from that of other sea-ice types. The form drag of ridge keels has an important influence on sea-ice drift and deformation. In this study, both laboratory experiment (LabE) and fluid dynamics numerical simulation (FDS) have been carried out for a physical ridge model in a tank to better understand the quantitative characteristics of the form drag. The LabEs covered both laminar and turbulent conditions. The local form drag coefficient of a keel, C-dw, varied with the keel depth h(w) and the slope angle alpha(w) in the turbulent regime. After validated by the LabE measurements, the FDSs were employed to extend the parameterization from the finite water depth to deep water. The results gave C-dw = 0.68 center dot ln (alpha(w)/7.8 degrees), R-2 = 0.998, 10 degrees = 0.01), the variation of the local form drag coefficient and its contribution to total drag coefficient were sensitive to the keel slope angle. Assuming the log-normal distribution for this angle, the average value of the local form drag coefficient was 0.75, recommended for sea-ice dynamic models. Peer reviewed